Oropharyngeal resistome remains stable during COVID-19 therapy, while fecal resistome shifts toward a less diverse resistotype - Elizaveta V. Starikova; Yulia S. Galeeva; Dmitry E. Fedorov; Elena V. Korneenko; Anna S. Speranskaya; Oksana V. Selezneva; Polina Y. Zoruk; Ksenia M. Klimina; Vladimir A. Veselovsky; Maxim D. Morozov; Daria I. Boldyreva; Evgenii I. Olekhnovich; et al. (iScience)
Summary: Antimicrobial resistance poses a serious threat to global public health. The COVID-19 pandemic underscored the need to monitor the dissemination of antimicrobial resistance genes and understand the mechanisms driving this process. In this study, we analyzed changes to the oropharyngeal and fecal resistomes of patients with COVID-19 undergoing therapy in a hospital setting. A targeted sequencing panel of 4,937 resistance genes was used to comprehensively characterize resistomes. Our results demonstrated that the oropharyngeal resistome is homogeneous, showing low variability over time. In contrast, fecal samples clustered into two distinct resistotypes that were only partially related to enterotypes. Approximately half of the patients changed their resistotype within a week of therapy, with the majority transitioning to a less diverse and ermB-dominated resistotype 2. Common macrolide resistance genes were identified in over 80% of both oropharyngeal and fecal samples, likely originating from streptococci. Our findings suggest that the fecal resistome is a dynamic system that can exist in certain “states” and is capable of transitioning from one state to another. To date, this is the first study to comprehensively describe the oropharyngeal resistome and its variability over time, and one of the first studies to demonstrate the temporal dynamics of the fecal resistotypes.